1997
DOI: 10.1038/sj.leu.2400694
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated engraftment of human hematopoietic cells in severe combined immunodeficient mice following a single injection of Cl2MDP liposomes

Abstract: Transplantation of normal and malignant human hematopoietictherapeutic interventions in vivo. [13][14][15] Conditioning of SCID cells into severe combined immunodeficient (SCID) mice mice using sublethal TBI and intravenous transplantation allows for evaluation of long-term growth abilities of these cells allows for outgrowth of these cells in the SCID mouse boneand provides a preclinical model for therapeutic interventions.marrow. 1,16However, large numbers of cells are required for successful However, even f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…14,16,19,24,25 To our knowledge, there has been no previous comparison of NOD/SCID, SCID and Nude mice in their ability to permit growth of Raji, Daudi or Namalwa lymphoma cells. Previous studies of human leukemias comparing Nude and SCID mice demonstrated the superiority of SCID mice in supporting the growth of BALL-1, Molt-4, CEM and A-1 human leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,19,24,25 To our knowledge, there has been no previous comparison of NOD/SCID, SCID and Nude mice in their ability to permit growth of Raji, Daudi or Namalwa lymphoma cells. Previous studies of human leukemias comparing Nude and SCID mice demonstrated the superiority of SCID mice in supporting the growth of BALL-1, Molt-4, CEM and A-1 human leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of NOD/ SCID mice included the frequent occurrence of thymic lymphoma and discernable NK cell activity , which hindered execution of enduring engraftment. While various strategies had been evaluated co-transplantation of growth, only 70% of all AML samples exhibited detectible engraftment in NOD/SCID mice (Terpstra et al, 1997;Ailles et al, 1999;Bonnet et al, 1999;Rombouts et al, 2000b;Nitsche et al, 2003). The shortened life span of this strain (mean 8.5 months) also limited the duration of tumor watches (Ishikawa et al, 2007).…”
Section: Doimentioning
confidence: 99%
“…4,276,[374][375][376][377][378][379][380][381][382][383] Despite the obvious advantages of the NOD/SCID model over all other immunodeficient models, there are still some inherent obstacles. While various strategies, including hu-cytokine supplementation, 364,370,[384][385][386] co-transplantation of growth factor-producing cell lines or 'accessory cells' 384,385 have been evaluated, only 70% of all AML samples exhibit detectible engraftment in NOD/SCIDs. 364 Additionally, the development of thymic lymphomas by 8.5 months, 387 extreme radiosensitivity 387 and discernable NK cell activity 387 hinder execution of enduring engraftment.…”
Section: Nude Modelsmentioning
confidence: 99%